(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of this study evaluating biochemical effects and efficacy of optimized Hydralazine 25mg (F-6) as compared to placebo in adult hypertension patients Study Design: Randomized placebo-controlled trial, Double-blind Place and Duration of Study: This study was conducted at the Mohtarma Benazir Bhutto Shaheed Medical College, Biochemistry Department Mirpur, AJK from October 2014 to January 2015. Materials and Methods: In this study we selected 80 patients, from different hospital of Mirpur AJK and 20 patients take as placebo. We measured blood pressure at baseline and after 8 week for both groups that one group received Hydralazine 25mg (F-6) and one group received placebo. Biochemical safety parameter was also measured for both groups. In these parameters we studied protein proﬁle, enzymeselectrolytes, liver function, renal function and complete blood count. In basic metabolism we studied glucose metabolism and lipid metabolism in which triglycerides, LDL-cholesterol, HDL-cholesterol and total cholesterol was included. Microlab 300 was used for analysis of samples for both groups. Merck kits were used for analysis of sample. Results: Baseline systolic blood pressure for Hydralazine 25mg (F-6) was 148.8+ 10.2 and for placebo was 148.4+ 10.3. After 8 weeks was for Hydralazine 25mg (F-6) was 140.1 ± 10.4and for placebo was 148.2 ± 10.2. . Baseline Diastolic blood pressure for Hydralazine 25mg (F-6) was 97.6+ 6.3 and for placebo was 96.9+ 6.5. After 8 weeks was for Hydralazine 25mg (F-6) was 86.5 ± 5.9 and for placebo was 96.2 ± 5.9. Blood glucose was observed as no significant variations such as Fasting Blood Glucose (mg/dl) 98.8 ± 10.2 at base line and 98.7 ± 10.3 after 8 weeks. Lipid profile was also observed no significant variation. Such as Total Cholesterol (mg/dl) 196.8 ± 42.8 as baseline and 195.5 ± 42.6 after 8 weeks.LDL - Cholesterol (mg) 113.9 ± 32.5 at base line and 113.8 ± 32.6 after 8 weeks.HDL - Cholesterol (mg) 54.6 ± 12.5 at baseline and 54.6 ± 12.5 after 8 weeks, Triglycerides (mg) 138.3 ± 87.5 at baseline and 138.7 ± 88.1 after 8 weeks. The optimized product was observed best regarding glucose metabolism and also lipid metabolism because both biomolecule metabolisms remain unchanged and not affected with drug. Conclusion: Hydralazine 25mg (F-6) showed best result to achieve and maintain blood pressure for eight weeks. Due to high antihypertensive efficacy it is best choice for blood pressure patients and it is safe for metabolic syndrome patients